Daring to learn: a study on grandes écoles de commerce Françaises - Sineuil, Tiago Bertrand Marie de Vassal de (2021)
The Grandes Écoles de Commerce Françaises (GECF) have had their number of students steadily increase in the past three decades, faster than any other type of Grande École. Their rise in popularity is straightforward, once considered the positive advantages associated with a degree from one of those prestigious business schools. However, those advantages, especially the earnings premium, are not evenly distributed among GECF. The ones at the top (of which the most recognizable group is Les Trois Parisiennes, namely HEC Paris, ESSEC, and ESCP Europe) are disproportionately impacted in that regard. Two theories on returns of higher education compete to provide an explanation. Human Capital Theory states that higher ranked GECF are able to give a better education (in the broad sense, i.e. including but not restricted to coursework) to their students, which makes them more productive workers, and ultimately improves their prospects on the job market. On the other hand, Signalling Theory of Education supports the view that better schools are able to attract and select better students, therefore signalling their higher productivity to potential recruiters. The purpose of this study is to make sense of the opinion of French recruiters on the question. The goal is to understand how they fit in the Human Capital – Signalling framework, and which criteria they attribute more importance to. Although they hadn’t always thought of it in such formal terms, the opposition was understood by recruiters. On average, the preference for students from Les Trois Parisiennes was better explained by the selectiveness of the entrance exam; hence some evidence for the Signalling Theory of Education in that context.